1994
DOI: 10.1038/bjc.1994.463
|View full text |Cite
|
Sign up to set email alerts
|

Selected micronutrient intake and the risk of colorectal cancer

Abstract: SummaryThe relationship between estimated intake of selected micronutrients and the risk of colorectal cancer was analysed using data from a case-control study conducted in northern Italy. The There are indications that several micronutrients may influence the process of colorectal carcinogenesis. These include a potential protective effect of folate (Benito et al., 1991;Freudenheim et al., 1991), a co-factor in the methylation of thymidylate for DNA synthesis and the production of S-adenosylmethionine, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
79
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(84 citation statements)
references
References 18 publications
(30 reference statements)
2
79
1
1
Order By: Relevance
“…In two large female cohorts including both smokers and non-smokers, the Iowa Women's Health Study and the Nurses' Health Study, no significant association was observed between dietary intake of vitamin E and colorectal cancer risk (Willett et al, 1990;Bostick et al, 1993;Sellers et al, 1998). Case -control studies have yielded conflicting results: either inverse associations (Ferraroni et al, 1994;Ghadirian et al, 1997;La Vecchia et al, 1997) or no association has been observed (Freudenheim et al, 1990;Benito et al, 1991;Peters et al, 1992;Meyer & White, 1993;Olsen et al, 1994;Slattery et al, 1998). The intake level of dietary vitamin E in the present cohort was similar to that reported from other study populations (Peters et al, 1992;Slattery et al, 1998), and the intake level varied sufficiently: there was a 2.5-fold difference in median intake of vitamin E between the first and fourth quartile.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In two large female cohorts including both smokers and non-smokers, the Iowa Women's Health Study and the Nurses' Health Study, no significant association was observed between dietary intake of vitamin E and colorectal cancer risk (Willett et al, 1990;Bostick et al, 1993;Sellers et al, 1998). Case -control studies have yielded conflicting results: either inverse associations (Ferraroni et al, 1994;Ghadirian et al, 1997;La Vecchia et al, 1997) or no association has been observed (Freudenheim et al, 1990;Benito et al, 1991;Peters et al, 1992;Meyer & White, 1993;Olsen et al, 1994;Slattery et al, 1998). The intake level of dietary vitamin E in the present cohort was similar to that reported from other study populations (Peters et al, 1992;Slattery et al, 1998), and the intake level varied sufficiently: there was a 2.5-fold difference in median intake of vitamin E between the first and fourth quartile.…”
Section: Discussioncontrasting
confidence: 51%
“…In about half of the case -control studies, dietary carotenes have been inversely associated with colorectal cancer risk (van Poppel, 1993;Ferraroni et al, 1994;La Vecchia et al, 1997). In such studies, however, carotene intake may have been altered, either due to changes in dietary habits or changes in metabolism caused by the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Findings regarding the association of methionine with cancers of the breast, endometrium, and ovary have generally been null (Thorand et al, 1998;Shrubsole et al, 2001;Feigelson et al, 2003;Tworoger et al, 2006;Xu et al, 2007;Cho et al, 2007a), whereas for colorectal cancer, the findings have been mixed, with some suggesting an inverse association (Giovannucci et al, 1993(Giovannucci et al, , 1995(Giovannucci et al, , 1998 and others showing no association (Ferraroni et al, 1994;Slattery et al, 1997;Flood et al, 2002;Harnack et al, 2002). We are unaware of any previous studies that have examined the association of methionine intake and lung cancer risk.…”
Section: Discussionmentioning
confidence: 71%
“…One small case -control study of colorectal cancer (Jedrychowski et al, 2002) observed a significant inverse association with dietary thiamin intake but not with riboflavin intake. A second case -control study (Ferraroni et al, 1994) reported a significant inverse association of thiamin intake with colon cancer risk in both males and females, but found no association with niacin or folate intake. In a large case -control study from China (Xu et al, 2007), intake of riboflavin was not associated with endometrial cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective (Giovannucci et al, 1995;Glynn et al, 1996) and case-control studies of colorectal cancer (Freudenheim et al, 1991;Benito et al, 1991;Ferraroni et al, 1994) have also shown Serum folate, homocysteine and colorectal cancer risk in women: a nested caseÐcontrol study some inverse association with folate intake. In addition, red cell folate was inversely associated with the risk of developing colonic dysplasia or cancer among patients with ulcerative colitis (Lashner, 1993).…”
mentioning
confidence: 99%